A Randomized, Controlled Study of a Rural Sanitation Behavior Change Program in Madhya Pradesh, India - Patil, Sumeet R.; Arnold, Benjamin F.; Salvatore, Alicia; Briceno, Bertha; Colford, Jr., John M.; Gertler, Paul J. (World Bank, Washington, DC, 2014)
Poor sanitation and open defecation are thought to be a major cause of diarrhea and intestinal parasite infections among young children. In 1999, India launched the Total Sanitation Campaign with the goal of achieving universal toilet coverage in rural India by 2012. This paper reports on a cluster-randomized, controlled trial that was conducted in 80 rural villages in Madhya Pradesh to measure the effect of the program on toilet access, sanitation behavior, and child health outcomes. The study analyzed a random sample of 3,039 households and 5,206 children under five years of age. Field staff collected baseline measures of sanitation conditions, behavior, and child health, and re-visited households 21 months later. The analysis finds that implementation of the program activities was slower than the original timeline (only 35 percent of villages were triggered more than six months before the follow-up survey). Nevertheless, the Total Sanitation Campaign successfully increased toilet coverage by 19 percent in intervention villages compared with control villages (41 percent v. 22 percent), while reported open defecation decreased by 10 percent among adults (74 percent v. 84 percent). The intervention also led to some improvements in water quality and protozoan infection, but consistent improvements were not observed across multiple child health outcomes (diarrhea, helminth infections, child growth). However, the exposure period was likely to have been too short to result in any benefit of the sanitation interventions on child health. Given the large improvements in toilet construction documented, an additional follow-up survey with a longer period of exposure would yield valuable information on the effects of improved sanitation conditions on health outcomes.